The Response of Estuarine Ammonia-Oxidizing Communities to Constant and Fluctuating Salinity Regimes - Santos, João Pereira; Sousa, António G. G.; Ribeiro, Hugo; Magalhães, Catarina (Frontiers in Microbiology, 2020)
Aerobic nitrification is a fundamental nitrogen biogeochemical process that links the oxidation of ammonia to the removal of fixed nitrogen in eutrophicated water bodies. However, in estuarine environments there is an enormous variability of water physicochemical parameters that can affect the ammonia oxidation biological process. For instance, it is known that salinity can affect nitrification performance, yet there is still a lack of information on the ammonia-oxidizing communities behavior facing daily salinity fluctuations. In this work, laboratory experiments using upstream and downstream estuarine sediments were performed to address this missing gap by comparing the effect of daily salinity fluctuations with constant salinity on the activity and diversity of ammonia-oxidizing microorganisms (AOM). Activity and composition of AOM were assessed, respectively by using nitrogen stable isotope technique and 16S rRNA gene metabarcoding analysis. Nitrification activity was negatively affected by daily salinity fluctuations in upstream sediments while no effect was observed in downstream sediments. Constant salinity regime showed clearly higher rates of nitrification in upstream sediments while a similar nitrification performance between the two salinity regimes was registered in the downstream sediments. Results also indicated that daily salinity fluctuation regime had a negative effect on both ammonia-oxidizing bacteria (AOB) and ammonia-oxidizing archaea (AOA) community’s diversity. Phylogenetically, the estuarine downstream AOM were dominated by AOA (0.92–2.09%) followed by NOB (0.99–2%), and then AOB (0.2–0.32%); whereas NOB dominated estuarine upstream sediment samples (1.4–9.5%), followed by AOA (0.27–0.51%) and AOB (0.01–0.23%). Analysis of variance identified the spatial difference between samples (downstream and upstream) as the main drivers of AOA and AOB diversity. Our study indicates that benthic AOM inhabiting different estuarine sites presented distinct plasticity toward the salinity regimes tested. These findings help to improve our understanding in the dynamics of the nitrogen cycle of estuarine systems by showing the resilience and consequently the impact of different salinity regimes on the diversity and activity of ammonia oxidizer communities.